DESIGN OF SQUID ATRACTOR MADE FROM PALM FIBER BIOCOMPOSITE (ARRENGA PINNATA MERR) - Saputra, Adi; Sudrajat, Danu; Baskoro, Mulyono S. (Departemen PSP IPB, 2025)
Preserving sustainability of squid populations, applying technologies that support reproduction process of squids are essential. One promising technology that can be developed is using attractors as spawning media. The development of attractor technology must be carried out continuously, focusing on both design and the materials used. This study aims to design squid attractor using ijuk fiber biocomposites, expected to produce stronger and more environmentally friendly materials. The research methodology applies a comparative design approach analyzed descriptively. The results indicate that the constructed squid attractor demonstrates good stability and durability in aquatic environments while utilizing eco-friendly materials. Applying ijuk fiber as a substitute for fiberglass (mat and roving) in the attractor design has been successfully implemented. Therefore, the use of ijuk fiber as an alternative material for squid attractor construction is recommended as an innovative solution to support the sustainability of marine ecosystems. Key words: biocomposite, palm fiber, squid attractor, squid attractor design